Scalable production of nitrogen-doped carbons for multilayer lithium-sulfur battery cells. (May 2020) - Kensy, Christian; Härtel, Paul; Maschita, Johannes; Dörfler, Susanne; Schumm, Benjamin; Abendroth, Thomas; Althues, Holger; Lotsch, Bettina V.; Kaskel, Stefan
Abstract: Lithium-sulfur (Li–S) batteries are among the targeted candidates for future generation secondary batteries with high specific energy. Herein, a scalable synthesis is presented to produce highly porous, nitrogen-doped carbons from a commercial carbon black material by melamine impregnation and subsequent thermolysis. The process up-scaling up was demonstrated at > 100 g batch level. The nitrogen doping was controlled through pyrolysis temperatures and carbon to melamine ratio. The sulfur-carbon cathodes exhibit an enhanced cycle life at a moderate electrolyte to sulfur ratio of 7 μL mgS −1 . In particular, under lean conditions at low electrolyte amount of 5 μL mgS −1, the nitrogen functionalities improved active material utilization and capacity retention significantly. The nitrogen-doped scaffold was integrated into five-layered prototype cell (71 × 46 mm 2 ) with a capacity of up to 0.87 Ah reaching a specific energy density of 238 Wh kg −1 on stack level. These results provide new insights into realistic application of nitrogen-doped carbons on pouch cell level. Graphical abstract: Description : Highly porous, N-doped scaffolds produced from a commercial carbon black material were integrated into pouch cell reaching a specific energy density of 238 Wh kg −1 . Image 1 Highlights: Scalable finishing route to produce N-doped carbons by using melamine. Influence of nitrogen doping is analyzed electrochemically. Positive impact of N-doping was successful transferred from coin cell to pouch cell level. Prototype cell with a specific energy density of 238 Wh kg −1 is achieved.